Free convection in a trapezoidal enclosure divided by a flexible partition. (March 2020) - Mehryan, S.A.M.; Ghalambaz, Mohammad; Kalantar Feeoj, Reza; Hajjar, Ahmad; Izadi, Mohsen
Highlights: Free convection heat transfer in a trapezoidal enclosure is addressed. The enclosure is divided by a flexible partition. The Fluid–Stricture Interaction (FSI) approach with moving mesh is used. The finite element method is utilized to solve the governing equations. Effect of the flexibility of the partition on the thermal behavior is investigated. The increase of Rayleigh number increases the maximum tensions in the partition. Abstract: The Fluid-Structure Interaction (FSI) approach was utilized to model the displacement of a flexible partition in a trapezoidal enclosure due to interaction with an internal natural convection flow. A moving mesh technique, Arbitrary Lagrangian–Eulerian (ALE) method, is adopted to model the partition displacement and the flow and heat transfer in the enclosure. The finite element method is employed to solve the governing equations after transforming into a non-dimensional form. The effect of various non-dimensional parameters such as Rayleigh number, Prandtl number, trapezoidal walls inclination angles, and non-dimensional Young's modulus. The results show that the increase of Rayleigh number increases the heat transfer in the enclosure and the tension in the partition. Notably, raising Ra from 10 4 to 10 7 can increase the heat transfer rate in the cavity by 8 times. The inclination angle of cavity walls induces a minimal effect on the induced tensions in the partition while it influences the heat transfer. In particular, heat transfer rate in a square cavity is 15% higher than in a trapezoidal cavity having side walls with 30° angle of inclination.